Estimation of Carbon Stock in Mangrove Communities in Budo Village, Wori District, North Minahasa Regency - Ruru, Ricky Andreas; Rumengan, Antonius Petrus; Paransa, Darus Sa'adah Johanis; Paruntu, Carolus Paulus; Bara, Robert Antonius; Rondonuwu, Ari B. (Jurnal Ilmiah Platax, 2023)
Mangrove is an ecosystem consisting of a collection of trees and grows in the area around the coastline, living in conditions influenced by tides, muddy and sandy sediments. Has an important function in the effort to absorb carbon levels through the photosynthesis process which is better than other forest vegetation. The purpose of this study, namely to identify mangrove species, examine vegetation and determine the value of biomass and estimated carbon stock in Budo Village, Wori District, North Minahasa Regency, North Sulawesi. Data collection in this study used the line transect method with the transect position being on the left, middle and right of the mangrove ecosystem of Budo Village which was pulled along 100 meters per transect, then the quadrants were measured 10 m x 10 m using raffia rope to limit each quadrant with an interval of 10 m. m and the distance between transects is about 50 m. Based on the results of the study, found 4 types of mangroves, namely: Rhizophora mucronata, Rhizophora apiculata, Sonneratia alba, and Bruguiera gymnorrhyza. The highest density values and relative density of species were on transect 3 with a value of 900 trees/ha and 86.53% by Rhizophora apiculata. The species frequency and relative species frequency were highest in each transect owned by Rhizophora apiculata with values of 0.8 and 55.66%, respectively. The highest species cover was Rhizophora apiculata with a value of 2.56 cm/m with a relative species cover of 72.21%. The highest important value index was Rhizophora apiculata on transect 3 with a value of 214.31%. The highest biomass content was on transect 3 with a value of 592.27 tons/ha. The highest carbon content is on transect 3 with a value of 55.67 tons/ha.